Revitalisasi Hukum Ekonomi Syariah di Pesantren Madura Sebagai Resolusi Konflik Masyarakat - Harisah Harisah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractMadura is an area with many Islamic boarding schools as a place of Islamic scientific education. The state of the Madura pesantren is no longer only studying classical sciences. However, it has developed by examining modern sciences such as studies in several Madurese pesantren which have revitalized sharia economic law as studies, which are included in the scientific curriculum and equipped with institutional facilities to support learning in providing an overview of sharia economic practices. So that the modern program of the Madura boarding school has become one of the instruments of community conflict resolution in the economic field. This study uses qualitative methods by taking data through interviews and direct observation in the field. This study found that Islamic boarding schools in Madura have owned Islamic microfinance institutions as supporting learning of Islamic economic law to introduce scholarship and provision of sharia economic practices, so that students are able to apply Islamic economic values, as well as conflict resolution in the community in the economic field. While the programs in Madura Islamic boarding schools to become a forum for community conflict resolution are through several programs such as the study of muamalat fiqh books that are adjusted to the level of santri, in collaboration with education and training programs held by pondok-owned financial institutions to provide an overview of sharia economic practices, and employment programs for pesantren alumni. Whereas the program for the community in overcoming the economic conflicts of the community includes providing guidance on Islamic economics, in addition to providing financing facilities.Keywords: Sharia Economic Law, Islamic Boarding School, Resolution, Conflict. AbstrakMadura merupakan salah satu daerah dengan banyak pesantren sebagai salah satu tempat edukasi keilmuan Islam. Keadaan pesantren Madura ini tidak lagi hanya mengkaji ilmu-ilmu klasik. Akan tetapi sudah berkembang dengan mengkaji ilmu-ilmu modern seperti kajian di beberapa pesantren Madura yang telah merevitalisasi hukum ekonomi syariah sebagai kajian, yang dimasukkan dalam kurikulum keilmuan serta dilengkapi dengan fasilitas lembaga untuk menunjang pembelajaran dalam memberikan gambaran praktik ekonomi syariah. Sehingga program modern pesantren Madura ini telah menjadi salah satu instrumen resolusi konflik masyarakat dalam bidang ekonomi. Penelitian ini menggunakan metode kualitatif dengan pengambilan data melalui wawancara dan observasi langsung ke lapangan. Penelitian ini menemukan bahwa pondok pesantren di Madura telah memeliki lembaga keuangan mikro syariah sebagai penunjang pembelajaran hukum ekonomi syariah untuk mengenalkan keilmuan serta pembekalan praktik ekonomi syariah, sehingga santri mampu menerapkan nilai-nilai ekonomi syariah, serta menjadi resolusi konflik di masyarakat dalam bidang ekonomi. Sedangkan program-program yang ada di pesantren Madura untuk menjadi wadah sebagai resolusi konflik masyarakat yaitu melalui beberapa program seperti kajian kitab-kitab fikih muamalat yang disesuaikan dengan tingkatan santri, bekerja sama dengan diklat yang diadakan oleh lembaga keuangan milik pondok untuk memberikan gambaran praktik ekonomi syariah, serta program lapangan pekerjaan untuk alumni pesantren. Sedangkan program untuk masyarakat dalam mengatasi konflik ekonomi masyarakat antara lain mengadakan pembinaan tentang ekonomi syariah, selain memberikan fasilitas pembiayaan. Kata Kunci: Hukum Ekonomi Syariah, Pesantren, Resolusi, Konflik.